Blood glucose levels in diabetic patients following corticosteroid injections into the hand and wrist - Stepan, Jeffrey G. (2014)
PURPOSE: To quantify diabetic patients’ change in blood glucose levels after corticosteroid injection for common hand diseases and to assess which patient-level risk factors may predict an increase in blood glucose levels. METHODS: Patients were recruited for this case-crossover study in the clinic of fellowship-trained hand surgeons at a tertiary care center. Patients with diabetes mellitus type 1 or 2 receiving a corticosteroid injection recorded their morning fasting blood glucose levels for 14 days after their injection. Fasting glucose levels on days 1–7 after injection qualified as “case” data with levels on days 10–14 providing control data. A mixed model with a priori contrasts were used to compare post-injection blood glucose levels to baseline levels. A linear regression model was used to determine patient predictors of a post-injection rise in blood glucose levels. RESULTS: Forty of 67 patients (60%) recruited for the study returned completed blood glucose logs. There was a significant increase in fasting blood glucose levels following injection limited to post-injection days 1 and 2. Among patient risk factors in our linear regression model, type 1 diabetes and use of insulin each predicted a post-injection increase in blood glucose levels from baseline while higher HbA1c levels did not predict increases. DISCUSSION: Corticosteroid injections in the hand transiently increase blood glucose levels in diabetic patients. Patients with type 1 diabetes and insulin-dependent diabetics are more likely to experience this transient rise in blood glucose levels. LEVEL OF EVIDENCE: Therapeutic Level III